2016
DOI: 10.1177/1932296816629158
|View full text |Cite
|
Sign up to set email alerts
|

Current and Next Generation Portable Screening Devices for Diabetic Retinopathy

Abstract: Diabetic retinopathy (DR) is the leading cause of legal blindness in the United States, and with the growing epidemic of diabetes, a global increase in the incidence of DR is inevitable, so it is of utmost importance to identify the most costeffective tools for DR screening. Emerging technology may provide advancements to offset the burden of care, simplify the process, and provide financially responsible methods to safely and effectively optimize care for patients with diabetes mellitus (DM). We review here c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 30 publications
1
38
0
Order By: Relevance
“…The same objective is targeted in the work described in [25] that compares the "fundus on phone' (FOP) and 7-standard field digital retinal photography to detect DR severity. Even the poor quality in some fundus images captured by FOP images, this study does not report a signification difference on the detection performance where the correspondence metric «Kappa » between both evaluations is equal to 90%.The work described in [27] evaluates the capability of the D-Eye device to allow detecting the DR. The authors report that fundus image quality is not enough higher to detection the DR, but indicates that the technological advances will improve the Smartphone fundus photography capabilities.…”
Section: Smartphone-captured Fundus Image Capabilitymentioning
confidence: 71%
See 2 more Smart Citations
“…The same objective is targeted in the work described in [25] that compares the "fundus on phone' (FOP) and 7-standard field digital retinal photography to detect DR severity. Even the poor quality in some fundus images captured by FOP images, this study does not report a signification difference on the detection performance where the correspondence metric «Kappa » between both evaluations is equal to 90%.The work described in [27] evaluates the capability of the D-Eye device to allow detecting the DR. The authors report that fundus image quality is not enough higher to detection the DR, but indicates that the technological advances will improve the Smartphone fundus photography capabilities.…”
Section: Smartphone-captured Fundus Image Capabilitymentioning
confidence: 71%
“…Moreover, the autofocus and the zooming option facilitate the acquisition and lead to provide a fundus image good quality [25]. With data capability, connectivity and portability, the capture devices represent promising tools for screening fundus images and diagnosing ocular diseases, which can be employed for tele-ophtalmology [21,22,25,27]. The captured images and videos may be sent to ophthalmologists to be saved and interpreted.…”
Section: Advantages Of Smartphone Fundus Image Capturing For Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been substantial effort in recent years to incorporate smartphone-based devices in screening and monitoring of diseases such as glaucoma and diabetic retinopathy (DR) [13][14][15] While these results are encouraging, the prior literature has not addressed whether handheld retinal photography could be made simple and intuitive for non-expert operators in non-ideal settings. Indeed, experience with our first generation Ocular CellScope prototype demonstrated that smartphone imaging of the retina, while highly possible, could also be highly variable.…”
Section: Discussionmentioning
confidence: 99%
“…There is particularly great interest in the validation and integration of smartphone-based retinal photography in local community screening programs for diseases such as glaucoma and diabetic retinopathy (DR) [13][14][15][16] , as well as in the emergency department and inpatient settings where the fundus examination is under-performed [17][18][19] . DR is the most common microvascular complication of diabetes and the leading cause of vision loss in working-age adults aged 20 to 74 in the United States, accounting for 12% of new cases annually [20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%